Outcomes of Metabolic Surgeries with Special Reference to Weight Loss, Diabetes Mellitus, Hypertension, and Thyroid Profile - Abhishek Singh Rathore; Dheeraj Raj; Yogita Singh; Vishwa Bandhu (Wolters Kluwer Medknow Publications, 2024)
Background: Metabolic surgery, which results in significant weight loss and the improvement, prevention, or remission of multiple related conditions including type 2 diabetes, heart disease, hypertension, sleep apnea, and various malignancies, is the most effective and long-lasting therapy for excessive obesity. Aims and Objectives: To examine the results of metabolic operations with an emphasis on thyroid function, weight reduction, diabetes mellitus, and hypertension. Material and Methods: From June 2021 to June 2022, thirty-two (15 men and 17 women) patients were selected from the outpatient division of state-run Government Medical College. It is a case series analysis on patients who underwent bariatric surgeries which were conducted after clinical history and clinical examination with appropriate investigations on those patients who were admitted. The study only covered those who had no significant organ involvement and those who met the inclusion criteria were invited to take part in the study. Results: About 32 individuals underwent metabolic surgeries in the General Surgery department, at SVBP Hospital affiliated with LLRM Medical College Meerut. The difference between various parameters, such as pre-op and post-op, is compared using the various statistical analysis between the single group that differs from a known mean value. Conclusion: Metabolic surgery is presently the most effective treatment for attaining long-term weight loss and has been demonstrated to benefit T2DM thyroid and Hypertensive patients. Our study supports the statistical significance of variables including hemoglobin, BMI, HbA1c, serum creatinine, total cholesterol, LDL, SBP, and TSH.